Multi-source solid waste filling slurry and preparation method thereof

By combining a variety of industrial solid waste materials with gelling materials such as water-based epoxy resins, a multi-source solid waste filling slurry was developed, which solved the problems of high cost of existing mine filling materials and environmental pollution, achieved low-cost and high-performance filling effects, and promoted the greening process of coal mining.

CN119613069AActive Publication Date: 2025-03-14HENGYANG CHUANGFEI ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411818334.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing mine filling materials are cement as the main cementitious material, which is costly and environmentally contaminated, and the mechanical properties need to be improved. At the same time, the utilization rate of industrial solid waste materials is low, occupying land resources and seriously polluting.

Method used

Develop a multi-source solid waste filling slurry, using a variety of industrial solid waste materials such as tailings, desulfurization gypsum, gasification slag, etc. as aggregates, and combined with gelling materials such as aqueous epoxy resin, aqueous acrylic resin, polyacrylic acid, etc. to form a low-cost and high-performance filling slurry.

Benefits of technology

The mineral filling without cement has been achieved, cost and environmental pollution has been reduced, the mechanical properties and resource utilization of the filling body have been improved, and the greening process of coal mining has been promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613069A_ABST
    Figure CN119613069A_ABST
Patent Text Reader

Abstract

The invention discloses multi-source solid waste filling slurry and a preparation method thereof, and belongs to the technical field of green filling mining of coal mines. The multi-source solid waste filling slurry is prepared from the following raw materials: a multi-source solid waste material, water-borne epoxy resin, a curing agent, water-borne acrylic resin and polyacrylic acid, the multi-source solid waste material comprises the following raw materials: tailings, desulfurized gypsum, fly ash and gasified slag. The used raw materials are all green and environment-friendly raw materials, various solid waste materials are low in cost, cement does not need to be added in the whole preparation process, the coal mine filling and mining cost is effectively reduced, various solid waste materials are efficiently and reasonably used, ground surface accumulation is reduced, and the green mining process of coal is greatly promoted; a brand-new green filling path is provided for cemented filling mining, and wide social benefits and economic benefits are achieved on the aspect of guaranteeing safe and low-cost mining of mines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green filling mining of coal mines, and in particular to a multi-source solid waste filling slurry and a preparation method thereof. Background Art

[0002] In the context of the growing demand for energy today, coal, as a conventional energy source with abundant reserves, wide distribution and relatively low price in the world, plays a vital role in many industries such as electricity, metallurgy, building materials, and chemicals. However, with the continuous development of coal resources, a series of serious problems have gradually emerged. The emergence of mine goafs often leads to surface subsidence and unstable mine pressure. The subsidence and collapse of the ground in the goafs can easily cause major disasters such as instability of the mining site, posing a serious threat to the safety of the mining area and its surrounding areas. At the same time, a large amount of industrial solid waste materials will be generated in the process of coal utilization. These solid waste materials not only occupy precious land resources, but also cause great pollution to the ecological environment.

[0003] In order to solve the problem of mining subsidence, mine filling technology came into being. Mine filling requires a large amount of high-quality filling materials, and the current existing mine filling materials are mainly mixed slurries such as gangue, cement, and fly ash. However, as a commonly used cementing material, cement is relatively expensive, and the large-scale use of cement will undoubtedly greatly increase the cost of mine filling. Moreover, a large amount of carbon dioxide will be produced during the production process of cement, and the large-scale use of cement is not conducive to environmental protection. In addition, the mechanical properties of filling materials using cement as a cementing material need to be improved. Therefore, it is imperative to develop an economical and excellent mechanical properties of filling materials.

[0004] Moreover, with the rapid development of industry and the continuous evolution of cities, the output of industrial solid waste is increasing day by day. The large accumulation of these industrial solid waste materials not only occupies a large amount of land resources, but also becomes a serious source of pollution, causing great harm to the environment and ecology. How to achieve the rational utilization of industrial solid waste has become a key issue that needs to be solved urgently.

[0005] In summary, if we can use industrial solid waste as the main raw material to develop an economical, efficient and environmentally friendly mine filling material that does not use cement, it will have great development prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-source solid waste filling slurry and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The multi-source solid waste filling slurry uses tailings, desulfurized gypsum and gasified slag as aggregates, and water-based epoxy resin and its curing agent, water-based acrylic resin, polyacrylic acid and fly ash as cementitious materials. It makes full use of multi-source solid waste materials and combines the excellent properties of water-based epoxy resin, water-based acrylic resin and polyacrylic acid to obtain a low-cost, high-performance filling slurry, which provides an economical, efficient and environmentally friendly solution for mine filling. The multi-source solid waste filling slurry uses a variety of industrial solid waste materials as the main components, and can efficiently utilize multi-source solid waste to achieve the best rationality of solid waste filling.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention: a multi-source solid waste filling slurry, the raw materials of which include: multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid;

[0009] In terms of mass percentage, the raw materials of the multi-source solid waste materials include: 38-45% tailings, 18-24% desulfurized gypsum, 19-24% fly ash and 11-15% gasified slag;

[0010] The sum of the mass of the waterborne epoxy resin and the curing agent is 7.5-12.5% ​​of the mass of the multi-source solid waste material;

[0011] The mass of the water-based acrylic resin is 2-5% of the mass of the multi-source solid waste material;

[0012] The mass of the polyacrylic acid is 0.5-1% of the mass of the multi-source solid waste material.

[0013] The filling slurry of the present invention uses multi-source solid waste materials composed of tailings, desulfurized gypsum, fly ash and gasified slag as the main raw materials. The microscopic morphology of tailings is generally a regular block structure, with a rough surface and a high specific surface area. Its particle size is large, and it is the most used solid waste material in the filling slurry. Tailings not only play a role in skeleton support, but also, due to the microscopic characteristics of its surface, it helps to effectively adhere to hydrated gelling materials such as water-based epoxy resin, thereby improving the overall bonding strength and structural stability of the filling body. The microscopic morphology of desulfurized gypsum is generally an irregular plate-like or sheet-like structure, which is conducive to its interlaced superposition in the filling slurry system, providing a certain structural stability and filling property for the filling slurry system. And its specific surface area is large, which can better physically adsorb and chemically react with other substances (such as gelling materials, etc.), promote the coagulation and hardening process of the material, and enhance the overall strength and durability of the material. The microscopic morphology of fly ash is generally spherical, with a relatively smooth surface and a porous structure, which can absorb more hydration products to improve the strength and durability of the filling body. The microscopic morphology of gasified slag presents irregular blocks, porous structures and rough surfaces. These characteristics make gasified slag have good filling, adsorption, strength support and certain chemical reaction activity in the filling body, which can improve the performance of the filling body. The use of these multi-source solid waste materials lays the foundation for the good mechanical properties of the filling body prepared by filling slurry. In addition, the water-based epoxy resin and its curing agent used in the filling slurry work synergistically to effectively improve the performance of the solid waste material. The water-based epoxy resin plays a key bonding and reinforcing role in the filling slurry. It has good bonding properties and can tightly combine various solid waste materials to form a solid filling structure. At the same time, the water-based epoxy resin can also improve the water resistance, corrosion resistance and durability of the filling body. The water-based epoxy resin curing agent is used in combination with the water-based epoxy resin to promote the curing reaction of the epoxy resin, form a stable three-dimensional network structure, and further enhance the strength and stability of the filling body. The water-based acrylic resin has a good adhesion effect on solid waste materials such as tailings, gasified slag, desulfurized gypsum, and fly ash. It can assist the water-based epoxy resin to strengthen the adhesion between each aggregate and the cementitious material, and better reduce the voids in the filling body. Polyacrylic acid has a higher degree of anchoring of particulate matter, which can make the bonded objects more stable, and can reduce the holes and cracks in the filling body for a second time, so that the performance of the filling body is further improved. The multi-source solid waste filling slurry makes full use of a variety of solid waste materials, and works together with water-based epoxy resin and its curing agent, water-based acrylic resin, and polyacrylic acid. It can reduce the use of water-based epoxy resin and its curing agent as much as possible without introducing additional stimulants, greatly reducing the filling cost. Especially under a specific dosage range and specific concentration conditions, the specific raw material combination ratio works together to promote the further improvement of the comprehensive performance of the filling body such as the compressive strength. The present invention obtains low-cost and high-performance filling slurry without using cement.

[0014] Furthermore, the raw materials of the multi-source solid waste filling slurry also include a defoamer; the mass of the defoamer is 2% of the sum of the mass of the dry matter of the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid.

[0015] Furthermore, the defoaming agent includes organosilicon and tributyl phosphate; the mass ratio of the organosilicon to the tributyl phosphate is 1:2.

[0016] As a defoamer, organosilicon can effectively eliminate bubbles generated during the preparation process, improve the density and uniformity of the filling body prepared using multi-source solid waste filling slurry, and thus improve the performance of the filling body. As a defoamer, tributyl phosphate works synergistically with organosilicon to ensure that the filling slurry maintains good performance during the preparation process and further reduce the impact of bubbles on the quality of the filling body.

[0017] Further preferably, the raw materials of the multi-source solid waste filling slurry include: multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin, polyacrylic acid and defoaming agent;

[0018] The sum of the mass of the waterborne epoxy resin and the curing agent is 7.5-10% of the mass of the multi-source solid waste material;

[0019] The mass of the water-based acrylic resin is 4-5% of the mass of the multi-source solid waste material;

[0020] The mass of the polyacrylic acid is 0.75% of the mass of the multi-source solid waste material;

[0021] The mass of the defoaming agent is 2% of the sum of the mass of the dry matter of the multi-source solid waste material, the water-based epoxy resin, the curing agent, the water-based acrylic resin and the polyacrylic acid.

[0022] As for the amount of waterborne epoxy resin and its curing agent, adding too much will result in high cost, while adding too little will affect the performance of the filling body. While saving costs, in order to meet practical applications, 7.5-12.5% ​​of the weight of waterborne epoxy resin and its curing agent is added to the multi-source solid waste material, and more preferably, the amount of waterborne epoxy resin and its curing agent added is 7.5-10%.

[0023] Furthermore, the particle size of the tailings is ≤2.5 mm.

[0024] Furthermore, the mass proportion of the components with a particle size of ≤4.75 mm in the gasified slag is higher than 98%.

[0025] Furthermore, the curing agent is a curing agent for water-based epoxy resin.

[0026] Furthermore, the waterborne epoxy resin is a bisphenol epoxy resin, and the curing agent includes an amine curing agent and / or an acid anhydride curing agent.

[0027] Technical solution 2 of the present invention: The method for preparing the multi-source solid waste filling slurry comprises the following steps:

[0028] After uniformly mixing the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid, adding water until the mass concentration of the multi-source solid waste filling slurry is 69-76%, stirring evenly, to obtain the multi-source solid waste filling slurry;

[0029] And / or, after the multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin, polyacrylic acid and defoaming agent are evenly mixed, water is added until the mass concentration of the multi-source solid waste filling slurry is 69-76%, and stirred evenly to obtain the multi-source solid waste filling slurry.

[0030] Further preferably, water is added to a mass concentration of the multi-source solid waste filling slurry of 73-76%.

[0031] The third technical solution of the present invention: application of the above-mentioned multi-source solid waste filling slurry in mine filling.

[0032] The present invention discloses the following technical effects:

[0033] (1) The filling slurry of the present invention does not contain cement, thus avoiding the large amount of carbon dioxide emissions generated during the cement production process. It is more environmentally friendly and economical than the traditional filling slurry using cement as the main cementitious material.

[0034] (2) The raw materials used in the present invention are all green and environmentally friendly raw materials, and various types of solid waste materials are low-cost. No cement needs to be added during the entire preparation process, which effectively reduces the cost of coal mine filling mining. In addition, various types of solid waste materials are used efficiently and rationally, which reduces surface accumulation and greatly promotes the green mining process of coal. It provides a new green filling path for cemented filling mining, and has broad social and economic benefits in ensuring safe and low-cost mining of mines.

[0035] (3) The filling slurry preparation process of the present invention is simple, and the water-based epoxy resin and its curing agent can be diluted arbitrarily by adding water. Therefore, the formula and preparation process can be adjusted according to different engineering scenarios such as mine filling, and it has strong adaptability and flexibility.

[0036] (4) The filling slurry of the present invention uses water-based epoxy resin and its curing agent as the main gelling materials. Compared with traditional organic solvent-based resins, water-based epoxy resins are non-toxic, odorless, and pollution-free, meet environmental protection requirements, and can be used in combination with multi-source solid waste materials, thereby reducing the occupation of land resources and pollution to the environment by industrial solid waste, realizing the recycling of resources, and having significant environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 is the XRD diffraction pattern of the tailings used in the embodiments of the present invention;

[0039] Figure 2 is a SEM image of the tailings used in the embodiments of the present invention;

[0040] Figure 3 is the XRD diffraction pattern of the desulfurized gypsum used in the embodiment of the present invention;

[0041] Figure 4 This is a SEM image of the desulfurized gypsum used in the embodiments of the present invention;

[0042] Figure 5 is the XRD diffraction pattern of fly ash used in the embodiments of the present invention;

[0043] Figure 6 is a SEM image of fly ash used in the embodiments of the present invention;

[0044] Figure 7 The XRD diffraction pattern of the gasified slag used in the embodiments of the present invention is;

[0045] Figure 8 is a SEM image of the gasified slag used in the embodiment of the present invention;

[0046] Fig. 9 This is a SEM image of a filling body made using the filling slurry prepared in Example 1, with a scale of 20.0 μm;

[0047] Fig.10 This is a SEM image of a filling body made using the filling slurry prepared in Example 1, with a scale of 10.0 μm;

[0048] Fig.11 This is a SEM image of a filling body prepared using the filling slurry prepared in Example 1, with a scale of 1.0 μm. DETAILED DESCRIPTION

[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0054] As a first aspect of the present invention, the present invention provides a multi-source solid waste filling slurry, the raw materials of which include: multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid;

[0055] In terms of mass percentage, the raw materials of the multi-source solid waste materials include: 38-45% tailings, 18-24% desulfurized gypsum, 19-24% fly ash and 11-15% gasified slag;

[0056] The sum of the mass of the waterborne epoxy resin and the curing agent is 7.5-12.5% ​​of the mass of the multi-source solid waste material;

[0057] The mass of the water-based acrylic resin is 2-5% of the mass of the multi-source solid waste material;

[0058] The mass of the polyacrylic acid is 0.5-1% of the mass of the multi-source solid waste material.

[0059] As a preferred embodiment of the present invention, the raw materials of the multi-source solid waste filling slurry also include a defoamer; the mass of the defoamer is 2% of the sum of the dry matter mass of the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid.

[0060] As a preferred embodiment of the present invention, the defoaming agent includes organosilicon and tributyl phosphate; the mass ratio of the organosilicon to the tributyl phosphate is 1:2.

[0061] As a preferred embodiment of the present invention, the waterborne epoxy resin is a bisphenol-type waterborne epoxy resin. Waterborne epoxy resin refers to a stable dispersion system in which epoxy resin is dispersed in a dispersion medium with water as a continuous phase in the form of particles or droplets. That is, a stable dispersion system in which epoxy resin is dispersed in water by introducing hydrophilic groups or using emulsifiers as the main component. Its main components include epoxy resin, and additives such as hydrophilic groups introduced or emulsifiers used to make epoxy resin hydrophilic. It contains groups such as epoxy groups and hydroxyl groups.

[0062] As an embodiment of the present invention, the curing agent is a curing agent for waterborne epoxy resin, that is, a substance that can react with waterborne epoxy resin to cure it, mainly including compounds such as amines and acid anhydrides, and mainly containing groups such as amino groups and carboxyl groups.

[0063] As an embodiment of the present invention, the waterborne epoxy resin is the waterborne epoxy resin component in a two-component waterborne epoxy resin, and the curing agent is the curing agent component in the two-component waterborne epoxy resin.

[0064] As an embodiment of the present invention, the water-based acrylic resin is mainly formed by polymerization of acrylic ester monomers and other vinyl monomers, and its main components are acrylic ester, methacrylic ester, vinyl monomers and water-based monomers.

[0065] As an embodiment of the present invention, the polyacrylic acid is a water-soluble high molecular polymer, and its molecular chain contains a large number of strong polar groups such as carboxyl groups, and its chemical formula is (C 3 H 4 O 2 ) n .

[0066] As an embodiment of the present invention, the organosilicon is a type of organic compound containing silicon element, which has excellent heat resistance, weather resistance and water resistance, etc., and its main structural feature is containing silicon-oxygen bonds, etc.

[0067] As an embodiment of the present invention, the tailings are waste discharged after the ore is ground and useful components are selected in the ore dressing plant under specific economic and technical conditions. The main crystalline mineral components in the tailings are SiO 2 .

[0068] As an embodiment of the present invention, the desulfurized gypsum is a byproduct produced by thermal power plants, chemical enterprises, etc. after desulfurization of sulfur-containing flue gas under specific environmental protection technology (limestone-gypsum wet desulfurization) conditions. The main crystalline mineral component in the desulfurized gypsum is CaSO 4 ·2H 2 O, other crystalline mineral components have a small amount of CaCO 3 .

[0069] As an embodiment of the present invention, the fly ash refers to the fine ash collected from the flue gas after coal combustion, which is the main solid waste discharged from coal-fired power plants. The main crystalline mineral components are SiO 2 , other crystalline minerals are Al 2 SiO 5 、AlPO 4 、A1 2 O 3 .

[0070] As an embodiment of the present invention, the gasified slag is produced by incomplete combustion of coal with oxygen or oxygen-enriched air to generate CO and H 2 During the process, the inorganic minerals in the coal undergo different physical and chemical transformations, and the solid residues formed along with the carbon particles remaining in the coal are mainly composed of C 30 H 14 N 4 O 4 Zn·2H 2 O.

[0071] As a preferred embodiment of the present invention, the particle size of the tailings is ≤2.5 mm.

[0072] As a preferred embodiment of the present invention, the mass proportion of the components with a particle size of ≤4.75 mm in the gasified slag is higher than 98%.

[0073] As a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned multi-source solid waste filling slurry, comprising the following steps:

[0074] After uniformly mixing the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid, adding water until the mass concentration of the multi-source solid waste filling slurry is 69-76%, stirring evenly, to obtain the multi-source solid waste filling slurry;

[0075] And / or, after the multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin, polyacrylic acid and defoaming agent are evenly mixed, water is added until the mass concentration of the multi-source solid waste filling slurry is 69-76%, and stirred evenly to obtain the multi-source solid waste filling slurry.

[0076] As a preferred embodiment of the present invention, water is added to the multi-source solid waste filling slurry to a mass concentration of 73-76%.

[0077] As a third aspect of the present invention, the present invention provides the use of the above-mentioned multi-source solid waste filling slurry in mine filling.

[0078] The multi-source solid waste filling slurry and the preparation method thereof of the present invention are further described below in conjunction with specific embodiments.

[0079] The raw materials used in the following examples and comparative examples were purchased from the market, wherein:

[0080] The XRD diffraction pattern of the tailings used is shown in Figure 1 , SEM images are shown in Figure 2 ,Depend on Figure 1 It can be seen that the maximum diffraction peak appears between 20° and 30° in the XRD diffraction spectrum, and there are smaller diffraction peaks at other angles, indicating that the crystalline mineral components in the tailings are mainly SiO 2 , other crystalline minerals are present in smaller amounts;

[0081] Depend on Figure 2 From the SEM image of the tailings, it can be seen that the tailings microstructure presents a relatively regular polyhedral block structure, which can provide a stable skeleton support for the filling body; and its surface has obvious concave-convex texture, is relatively rough, and has a large surface area, which enables the tailings to be closely combined with the hydrated gelling material during the formation of the filling body, so that the various parts of the filling body are more firmly bonded, and finally form a higher strength overall sample;

[0082] The XRD diffraction pattern of the desulfurized gypsum used is shown in Figure 3 , SEM images are shown in Figure 4 ,Depend on Figure 3 It can be seen that the maximum diffraction peak appears between 10° and 55° in the XRD diffraction spectrum, and there are other diffraction peaks, indicating that the main crystalline mineral component of desulfurized gypsum is CaSO 4 ·2H 2 O, other crystalline mineral components contain CaCO 3 ;

[0083] Depend on Figure 4From the SEM image of desulfurized gypsum, it can be seen that the microscopic morphology of desulfurized gypsum presents an irregular plate-like or flaky structure, which is conducive to the interlaced superposition in subsequent applications, providing a certain structural stability and filling property for the relevant material system; and its surface is relatively smooth, but there are some tiny pores and textures, which increase its specific surface area, so that when used as a building material or industrial filler, desulfurized gypsum can better physically adsorb and chemically react with other substances (such as cementitious materials, additives, etc.), promote the coagulation and hardening process of the material, and enhance the overall strength and durability of the material;

[0084] The XRD diffraction pattern of the fly ash used is shown in Figure 5 , SEM images are shown in Figure 6 ,Depend on Figure 5 It can be seen that the XRD diffraction spectrum has the largest diffraction peak between 20° and 30°, and there are multiple other diffraction peaks between 30° and 45°, indicating that the main crystalline mineral component of fly ash is SiO 2 , other crystal mineral components are A1 2 SiO 5 、AlPO 4 、Al 2 O 3 ;

[0085] Depend on Figure 6 From the SEM image of fly ash, it can be seen that the microscopic morphology of fly ash is spherical. The surface of these spherical particles is relatively smooth and of different sizes. The surface has a porous structure. The size and shape of these pores are different, so more hydration products can be adsorbed to improve the strength and durability of the filling body.

[0086] The XRD diffraction pattern of the gasified slag used is shown in Figure 7 , SEM images are shown in Figure 8 ,Depend on Figure 7 It can be seen that the XRD diffraction spectrum only has the largest diffraction peak between 20° and 30°, and it is the only diffraction peak in the spectrum, indicating that the mineral composition of the fumed slag is single, and the main component is C 30 H 14 N 4 O 4 Zn·2H 2 O;

[0087] Depend on Figure 8 It can be seen from the SEM image of the gasified slag that the microstructure of the gasified slag presents irregular blocks, porous structure and rough surface; these characteristics make the gasified slag have good filling properties, adsorption properties, strength support and certain chemical reaction activity in the filling body, which can improve the performance of the filling body.

[0088] The particle size statistics of the tailings and gasified slag used in the specific embodiments and comparative examples of the present invention are shown in Table 1 (where % is mass percentage), and the particle size range of other raw materials is not limited.

[0089] Table 1

[0090]

[0091] The water-based epoxy resin used was epoxy emulsion HT-5150, purchased from Hubei Jinshengyuan Environmental Protection Technology Co., Ltd.;

[0092] The curing agent used was curing agent G08, purchased from Hubei Jinshengyuan Environmental Protection Technology Co., Ltd.;

[0093] The mass ratio of the waterborne epoxy resin to its curing agent in each embodiment and comparative example is 2:1;

[0094] The aqueous acrylic resin used was aqueous acrylic emulsion E0504, purchased from Shenzhen Yoshida Chemical Co., Ltd.;

[0095] The polyacrylic acid used was polyacrylic acid DL-03, purchased from Jinan DeLan Chemical Co., Ltd.;

[0096] The organic silicon used was industrial defoamer CI-0560, purchased from Guangdong Nanhui New Materials Co., Ltd.;

[0097] The molecular weight of the tributyl phosphate used was 266.31 and was purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.

[0098] Example 1

[0099] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0100] Multi-source solid waste materials are weighed according to the mass percentage of 45% tailings, 20% desulfurized gypsum, 20% fly ash, and 15% gasified slag, and water-based epoxy resin and its curing agent accounting for 10% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 3% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.75% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate (the mass ratio of silicone and tributyl phosphate is 1:2) accounting for 2% of the total mass of dry matter (the sum of the mass of multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid). After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0101] Example 2

[0102] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0103] Multi-source solid waste materials are weighed according to the mass percentage of 43% tailings, 22% desulfurized gypsum, 20% fly ash and 15% gasified slag, and water-based epoxy resin and its curing agent accounting for 10% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 3% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.75% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0104] Example 3

[0105] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0106] Multi-source solid waste materials are weighed according to the mass percentage of 38% tailings, 24% desulfurized gypsum, 24% fly ash, and 14% gasified slag, and water-based epoxy resin and its curing agent accounting for 12.5% ​​of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 4% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 1% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0107] Example 4

[0108] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0109] Multi-source solid waste materials are weighed according to the mass percentage of 41% tailings, 23% desulfurized gypsum, 23% fly ash, and 13% gasified slag, and water-based epoxy resin and its curing agent accounting for 7.5% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 5% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.5% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0110] Example 5

[0111] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0112] Multi-source solid waste materials are weighed according to the mass percentage of 42% tailings, 20% desulfurized gypsum, 24% fly ash and 14% gasified slag, and water-based epoxy resin and its curing agent accounting for 10% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 2% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.75% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0113] Example 6

[0114] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0115] Multi-source solid waste materials are weighed according to the mass percentage of 45% tailings, 19% desulfurized gypsum, 23% fly ash and 13% gasified slag, and water-based epoxy resin and its curing agent accounting for 12.5% ​​of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 3% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 1% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing all the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0116] Example 7

[0117] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0118] Multi-source solid waste materials are weighed according to the mass percentage of 44% tailings, 22% desulfurized gypsum, 19% fly ash and 15% gasified slag, and water-based epoxy resin and its curing agent accounting for 7.5% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 4% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.5% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 74%.

[0119] Example 8

[0120] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0121] Multi-source solid waste materials are weighed according to the mass percentage of tailings 44%, desulfurization gypsum 18%, fly ash 23%, and gasification slag 15%, and water-based epoxy resin and its curing agent accounting for 10% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 5% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.75% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0122] Example 9

[0123] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0124] Weigh multi-source solid waste materials according to the following mass percentages: 43% tailings, 22% desulfurized gypsum, 24% fly ash, and 11% gasified slag, and weigh 12.5% ​​of the total mass of the multi-source solid waste materials, 2% of the total mass of the multi-source solid waste materials, 0.5% of the total mass of the multi-source solid waste filling materials, and 2% of the total mass of the dry matter, silicone and tributyl phosphate (the mass ratio of silicone and tributyl phosphate is 1:2). Mix the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0125] Comparative Example 1

[0126] The same as Example 1, the only difference is that the mass of tailings is replaced by gasified slag (that is, tailings are not used, and the amount of gasified slag becomes 60%).

[0127] Comparative Example 2

[0128] The same as Example 1, the only difference is that the desulfurized gypsum and other materials are replaced by tailings.

[0129] Comparative Example 3

[0130] The same as Example 1, the only difference is that the gasified slag and other masses are replaced by desulfurized gypsum.

[0131] Comparative Example 4

[0132] Same as Example 1, except that the desulfurized gypsum is replaced by cement (ordinary Portland cement P.O42.5).

[0133] Comparative Example 5

[0134] The same as Example 1, except that the water-based epoxy resin and its curing agent, as well as polyacrylic acid are replaced by water-based acrylic resin.

[0135] Comparative Example 6

[0136] The same as Example 1, except that the amount of water added is controlled to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 85%.

[0137] Comparative Example 7

[0138] A multi-source solid waste filling slurry, the preparation steps are as follows:

[0139] Multi-source solid waste materials are weighed according to the mass percentage of 55% tailings, 7% desulfurized gypsum, 10% fly ash and 28% gasified slag, and water-based epoxy resin and its curing agent accounting for 5% of the total mass of the multi-source solid waste materials, water-based acrylic resin accounting for 10% of the total mass of the multi-source solid waste materials, polyacrylic acid accounting for 0.25% of the total mass of the multi-source solid waste filling materials, and silicone and tributyl phosphate accounting for 2% of the total mass of dry matter (the mass ratio of silicone and tributyl phosphate is 1:2) are weighed. After mixing the raw materials evenly, add appropriate amount of water and mix and stir to obtain a multi-source solid waste filling slurry with a mass concentration (dry matter content) of 73%.

[0140] Comparative Example 8

[0141] Same as Example 1, except that the mass of polyacrylic acid is replaced by water-based acrylic resin.

[0142] Comparative Example 9

[0143] Same as Example 1, except that the water-based acrylic resin is replaced by water-based epoxy resin and its curing agent.

[0144] Comparative Example 10

[0145] The same as Example 1, except that the water-based epoxy resin and its curing agent, as well as the water-based acrylic resin and polyacrylic acid are replaced by cement (ordinary Portland cement PO 42.5) in equal mass.

[0146] Comparative Example 11

[0147] Same as Example 1, except that the organosilicon is replaced by tributyl phosphate.

[0148] Test Example 1

[0149] The filling slurries prepared in Examples 1-9 and Comparative Examples 1-11 were respectively prepared into filling bodies, and the compressive strength test was performed. The preparation method of the filling body was as follows: the filling slurry was slowly poured into a pre-prepared cylindrical mold of φ50×100 mm. In order to prevent bubbles from being generated again during the pouring of the slurry, the method of vibrating while pouring was adopted, and then the upper surface was smoothed with a shovel. The mold after pouring was placed in a cool place and left to stand for 2 days, and then demolding was performed. After the test piece was taken out, it was covered with a disposable plastic film and left to stand for (24±2)h in an environment of (20±5)℃, and then the test piece was numbered and demolded. After the test piece was demolded, it was first cured in a standard curing room (relative humidity above 92%) for 7 days, and then naturally cured in air (relative humidity 60%) for 28 days to obtain a filling body.

[0150] Figure 9-11 The SEM images of the filling body prepared by the filling slurry of Example 1 at different magnifications are shown in FIG. Figure 9-11 It can be seen that under the auxiliary bonding effect of water-based acrylic resin and polyacrylic acid, water-based epoxy resin and curing agent undergo cross-linking reaction to form a continuous three-dimensional network structure on the surface of the solid waste material, which produces an interlayer connection effect on the solid waste material, making it closely connected, greatly reducing the gaps between the solid waste materials, and thus improving the strength of the filling body.

[0151] The uniaxial compressive strength performance of the above-mentioned filling body was measured using a ZSC-107R rock triaxial creep system. The results are shown in Table 2.

[0152] Table 2

[0153]

[0154]

[0155] As can be seen from Table 2, by comparing Example 1 with Comparative Example 1, it can be found that after the tailings are replaced by gasified slag, the strength of the filling body decreases by 66.1%. This is because the tailings, as an important filling aggregate, play a huge role in supporting the filling body, while the gasified slag can play a certain macroscopic supporting role, but given that its main component is C 30 H 14 N 4 O 4 Zn·2H 2 O, and cannot provide SiO for the reaction of the gelling material 2, so that its macroscopic support effect is weaker than that of tailings. Comparing Example 1 with Comparative Example 2, it can be found that the strength of the filling body decreases by 59.5% when the desulfurized gypsum is replaced by tailings. This is because the tailings have large particles and a relatively rough surface, and the contact area with the cementitious material is relatively small, and the bonding effect is not as good as the desulfurized gypsum, resulting in the cementitious material being unable to fully exert its bonding and reinforcement effects, resulting in a decrease in the performance of the filling body. Comparing Example 1 with Comparative Example 3, it can be found that the strength of the filling body decreases by 59.7% when the gasified slag is replaced by desulfurized gypsum. This is because the gasified slag may have a higher reactivity and can react chemically with water-based epoxy resins, curing agents, etc. to form a more stable structure, while the reactivity of the desulfurized gypsum is relatively low, and the bonding with other materials is not tight enough, which reduces the strength of the filling body. Comparing Example 1 with Comparative Example 4, it can be found that the filling body strength decreased by 42.5% when desulfurized gypsum was replaced with cement. This is because the hydration reaction rate of cement is relatively fast, which may form a certain strength in the early stage, but in the multi-source solid waste filling body, too fast reaction may lead to internal stress concentration, affecting the development of later strength, while the reaction of desulfurized gypsum is relatively slow, and it may gradually form a stable structure with other materials over a long period of time, so that the filling body has better long-term strength. Comparing Example 1 with Comparative Example 5, it can be found that the filling body strength decreased by 49.3% when the water-based epoxy resin and its curing agent were replaced with water-based acrylic resin. This is because the bonding effect of water-based acrylic resin is worse than that of water-based epoxy resin and its curing agent and water-based acrylic resin, and a single water-based acrylic resin cannot bond various solid waste materials together well. Comparing Example 1 with Comparative Example 6, it can be found that when water is added, the mass concentration of the filling body reaches 85%, and the strength of the filling body is reduced by 52.9%. This is because too much water will change the hydration reaction process of various materials in the filling body. For the hydration reaction of fly ash, it is too fast or uneven, and the generated hydration product has a loose structure and cannot provide sufficient strength support. At the same time, excessive water may also wash away some of the incompletely reacted gelling substances, such as water-based epoxy resin and its curing agent, further reducing the strength of the filling body. Comparing Example 1 with Comparative Example 7, it can be found that Comparative Example 7 changes the amount of raw materials to exceed the scope of the claims, and the strength of the filling body is reduced by 64.6%, indicating that the excellent effects of various aspects of the filling slurry are reduced after changing the dosage range. Comparing Example 1 with Comparative Example 8, it can be found that replacing polyacrylic acid with water-based acrylic resin reduces the strength of the filling body by 55.1%. This is because compared with polyacrylic acid, the network structure formed by water-based acrylic resin in the filling body is not tight and perfect enough, and it cannot provide sufficient early strength and late strength growth for the filling body, resulting in a decrease in the mechanical properties of the filling body.Comparing Example 1 with Comparative Example 9, it can be found that the filling body strength decreased by 45.2% when the water-based acrylic resin was replaced with a water-based epoxy resin and its curing agent. This is because the water-based epoxy resin forms a relatively rigid three-dimensional network structure after curing. When the filling body resists external forces or internal stress changes, this rigid structure cannot absorb and disperse stress through deformation as effectively as the water-based acrylic resin, which easily leads to cracks in the filling body when it is subjected to a small deformation, reducing the crack resistance and overall stability of the filling body. Comparing Example 1 with Comparative Example 10, it can be found that the filling body strength decreased by 75.2% when the water-based epoxy resin and its curing agent, as well as the water-based acrylic resin and polyacrylic acid, were replaced with cement. This is because cement mainly bonds particles through the hydration products generated by the hydration reaction, and the bonding between it and the particles is mainly physical adsorption and weak chemical bonding, and its bonding method is relatively single. The bonding effect on particles such as tailings with relatively smooth surfaces or low chemical activity is not as good as that of water-based epoxy resins and their curing agents, as well as resin and polymer systems such as water-based acrylic resins and polyacrylic acid, resulting in reduced cohesion and integrity of the filling body. Comparing Example 1 with Comparative Example 11, it can be found that the strength of the filling body decreased by 43.6% when silicone was replaced with tributyl phosphate. This is because the defoaming effect of using tributyl phosphate alone is not good, resulting in more bubbles remaining inside the filling body. These bubbles will increase the porosity of the filling body and make the structure loose, thereby reducing the strength and stability of the filling body.

[0156] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A multi-source solid waste filling slurry, characterized in that: Ingredients include: Multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid; In terms of mass percentage, the raw materials of the multi-source solid waste materials include: 38-45% tailings, 18-24% desulfurized gypsum, 19-24% fly ash and 11-15% gasified slag; The sum of the mass of the waterborne epoxy resin and the curing agent is 7.5-12.5% ​​of the mass of the multi-source solid waste material; The mass of the water-based acrylic resin is 2-5% of the mass of the multi-source solid waste material; The mass of the polyacrylic acid is 0.5-1% of the mass of the multi-source solid waste material.

2. The multi-source solid waste filling slurry according to claim 1, characterized in that: The raw materials of the multi-source solid waste filling slurry also include a defoamer; the mass of the defoamer is 2% of the sum of the mass of the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid dry matter.

3. The multi-source solid waste filling slurry according to claim 2, characterized in that: The defoaming agent comprises organosilicon and tributyl phosphate; the mass ratio of the organosilicon to the tributyl phosphate is 1:

2.

4. The multi-source solid waste filling slurry according to claim 1, characterized in that: The particle size of the tailings is ≤2.5mm.

5. The multi-source solid waste filling slurry according to claim 1, characterized in that: The mass proportion of the components with a particle size of ≤4.75 mm in the gasified slag is higher than 98%.

6. The method for preparing multi-source solid waste filling slurry according to any one of claims 1 to 5, characterized in that: The following steps are involved: After uniformly mixing the multi-source solid waste material, water-based epoxy resin, curing agent, water-based acrylic resin and polyacrylic acid, adding water until the mass concentration of the multi-source solid waste filling slurry is 69-76%, stirring evenly, to obtain the multi-source solid waste filling slurry; And / or, after the multi-source solid waste materials, water-based epoxy resin, curing agent, water-based acrylic resin, polyacrylic acid and defoaming agent are evenly mixed, water is added until the mass concentration of the multi-source solid waste filling slurry is 69-76%, and stirred evenly to obtain the multi-source solid waste filling slurry.

7. Use of the multi-source solid waste filling slurry as described in any one of claims 1 to 5 in mine filling.

Citation Information

Patent Citations

  • Preparation method of expressway repairing material

    CN111484274A

  • Method for preparing filling material from multi-source coal-based solid waste

    CN113045282A

  • Slag-containing polymer concrete and grouting mortar

    CN113748095A

  • Epoxy resin-based permeable filling material as well as preparation method and application thereof

    CN114315263A

  • Filling slurry prepared from multi-source solid waste material and preparation method thereof

    CN116947449A

Cited By

  • Multi-source solid waste backfill slurry and preparation method therefor

    WO2026123658A1